2021
DOI: 10.35808/ijeba/726
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Taxation Policies on the Performance of Small to Medium Enterprises

Abstract: Purpose:The study investigates challenges faced by Small and Medium Enterprises (SMEs) in the introduction of new government taxation policies to financial performance of SMEs. Design/Methodology/Approach: Multiple regression model were used to measure the relationship between point of sale transaction tax, mobile money taxes and financial performance. SPSS and EXCEL were used to analyze the study data and to identify the descriptive characteristics of the dependent and independent variables and results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the same vein, increases in taxes are expected to reduce SME performance through a fall in investment income. This finding is similar to Ongayi et al (2021), who showed a negative effect of taxes on the financial performance of SMEs. In the long run, the positive effect of taxes on SME performance is suggestive of public use of tax funds for basic facilities, particularly in terms of key infrastructure that promotes business operations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the same vein, increases in taxes are expected to reduce SME performance through a fall in investment income. This finding is similar to Ongayi et al (2021), who showed a negative effect of taxes on the financial performance of SMEs. In the long run, the positive effect of taxes on SME performance is suggestive of public use of tax funds for basic facilities, particularly in terms of key infrastructure that promotes business operations.…”
Section: Discussionsupporting
confidence: 90%
“…When taxes are implemented to improve infrastructure and enhance business operations, positive effects are expected. However, where there is tax implementation with no associated infrastructure provision to reduce the overhead cost of operation, negative effects are expected (Ongayi et al, 2021). Hence, 0 < α 6 < 0.…”
Section: Model Specificationmentioning
confidence: 99%
“…Taxes are one of the most important constituents in revenue management at the national level [14]. Taxation is a key government policy measure and, therefore, has a direct impact on the operations of SMEs and their activities [15][16][17]. Moreover, as studies have shown [18], the tax burden is higher for SMEs compared to large and multinational enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The hut tax was the first formal tax introduced in 1900 for both Uganda and Kenya. Ugandans started paying customs duty as an indirect tax, which involved the imposition of an ad valorem import duty at a rate of 5% on all goods entering East Africa, through the port of Mombasa and destined for Uganda (Ongayi et al, 2021). Raude (2022) adds that the Protectorate government heavily relied on customs duties to fund its programs however it was insufficient to finance all the activities triggering a flat rate poll tax for all male adults.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Also, Arends (2020) noted that Decentralization refers to both a system and a process. (Ongayi et al, 2021) Through fiscal decentralization, Local revenue management is the planning of expenditure on local revenue. Local revenue refers to the total income generated by local administrative units in a decentralized system of government within a fiscal year (Mgonja & Poncian, 2019).…”
Section: Background Of the Studymentioning
confidence: 99%